PENGEMBANGAN MODUL BERBASIS KONSTRUKTIVISTIK PADA MATERI EKONOMI KELAS XI SEMESTER 2 SMA N 1 BANDAR SRIBHAWONO LAMPUNG TIMUR - Sulistiyani, Sulistiyani; Martono, Trisno; Riani, Asri Laksmi (Jurnal Pendidikan Insan Mandiri, 2016)
The objectives of this research are to analyze: (1) the validity of constructivist-based module on Economics learning material for Grade XI of Social Science Program in Semester 2, and (2) the effectiveness of  constructivist-based module on Economics learning material for Grade XI of Social Science Program in Semester 2.This research used the research and development (R&D) method to develop and expand the existing product in an attempt to generate a new accountable product. i.e. constructivist-based module on Economics learning material for Grade XI of Social Science Program in Semester 2 so as to improve the students? learning result in Economics. The research used the procedural development model claimed by Borg and Gall. Its population was all of the students as many as 165 in Grade XI of Social Science Program of State Senior Secondary School 1 of Bandar Sribhawono, Lampung Timur, in Academic Year 2014/2015. The samples of research were taken by using the purposive sampling technique. They consisted of 60 students: 30 in control class and 30 in experimental class.The developed constructivist-based module on Economics learning material for Grade XI of Social Science Program in Semester 2 is feasible to be used as it has fulfilled the required criteria in accordance with the guidelines for textbook assessment of the National Education Standard Agency (BSNP) of the Ministry of Education and Culture of the Republic of Indonesia 2014.  The developed constructivist-based module on Economics learning material for Grade XI of Social Science Program in Semester 2 is effective to improve the learning result of the students as indicated by the average score of the learning result of the control class and the experimental class, namely: 78.57 and 83.47 respectively. This indicates that the learning result of the experimental class is more excellent than that of the class control. The significance value of 2-tailed t test is 0.003, which is less than 0.050. Thus, the proposed H1 is rejected, meaning that there is a difference of score average in the learning result between the students of the control class and those of the experimental class, and the improvement of the learning result of the experimental class is better than that of the control class. Keywords: Module, constructivist, problem-based learning, and learning result.